Assessing the Role of Courtyards in the Spatial Organization of the Traditional Houses of Kashan - Nejadriahi, Halleh (Eastern Mediterranean University EMU, 2015)
Traditional houses of Iran possess significant qualities in terms of being responsive to the local context; not only from environmental aspects, but also by highly consideration of cultural values, and certainly, along with responding to the functional requirements of the inhabitants. Kashan as a city with 7000 years historical precedents encompasses a great number of traditional houses that worth to be studied in detail. The study of spatial organization of such houses is a fundamental issue in order to comprehend the topological relationships of the spaces, specifically based on the socio-cultural features. The study classifies and examines thirty traditional houses of Kashan by implementing several methods; mainly as schematic analysis of the houses and space syntax method, to clarify their spatial organizations. It should be mentioned that, courtyard that is known as the key component in the spatial organization of these houses is the basis of their classifications. Under this scope, the study is carried out in five chapters; the first chapter defines the problem and the necessity of such a study as well as the main objectives, and the process of handling the study. The second chapter provides information on the traditional residential architecture of Iran and its formation under the impacts of socio-cultural aspects as well as physical and environmental issues. Moreover, the general design principles and the main spaces in the traditional Iranian houses are explained. Following that the third chapter deals with the identification and evolution of Kashan city as the context of the study. Accordingly, some explanations are given regard to the location and climatic characteristics of the city along with its establishment and evolution throughout the history. In the fourth chapter, the traditional houses of Kashan are discussed in terms of their general architectural characteristics, and specifically on the existence of courtyard in them. Subsequently, the selected houses are classified, and analyzed through the schematic analysis, which clarifies some characteristics on their space organizations. Moreover, the spatial analysis of the houses is done by utilization of the space syntax method, which provides the syntactic data of the houses, and some findings and discussions are presented related to the inequality genotypes, rings, control values and generally verifying the role of courtyard in these houses. In conclusion, that is the fifth chapter; the results of the study are highlighted as well as the significance of comprehending the traditional architecture of the city in order to create identifiable contemporary architectural designs. In view of that, the traditional houses of Kashan and their specific characteristics should be sustained in order to achieve architectural continuity and maintain the identity of the city. Keywords: Spatial Organization, Courtyard, Traditional Houses, Kashan, Iran.

ÖZ: Geleneksel Iran evleri, çevreye gösterdiği duyarlılığın yanısıra, kültürel değerlere ve kullanıcılarının ihtiyaçlarına yönelik geliştirmiş olduğu çözümler nedeniyle yerel dokuya uygun önemli bir mimariye sahiptir. 7000 yıllık geçmişe sahip olan Kashan şehri çok sayıda geleneksel Iran evine ev sahipliği etmektedir. Bu tür evlerin mekansal organizasyonunun anlaşılması için doğru ve kapsamlı bir şekilde mekanların topolojik ilişkisi özellikle sosyo-kültürel değerler dikkate alınarak incelenmelidir. Bu çalışmada, geleneksel otuz Kashan evi, şematik analiz, mekansal sentaks gibi çeşitli yöntemler kullanılarak incelenmiş ve sınıflandırılmıştır. Bu tip evler mekansal organizasyonunda önemli bir unsur olarak Kabul edilen avlu, sınıflandırmanın temelini oluşturmaktadır. Bu bağlamda, çalışma beş bölümden oluşmaktadır. Birinci bölümde problem araştırma, çalışmanın gerekliliği, hedefleri ve süreçleri tanımlanmıştır. Çalışmanın ikinci bölümünde Iran geleneksel konut mimarisi ve sosyo-kültürel, fiziksel, çevresel değerlerin bu tip mimari üzerindeki etkileri hakkında bilgi verilmiştir. Ayrıca, geleneksel Iran evinin genel tasarım prensipleri ve başlıca temel mekanlar açıklanmıştır. Üçüncü bölümde, Kashan şehrinin oluşumu ve gelişimi çalışma kapsamında anlatılmıştır. Aynı kapsamda, tarihsel süreç boyunca şehrin konumu ve iklimsel özellikleri, kentin kuruluşu ve gelişimi açıklanmıştır. Dördüncü bölümde, geleneksel Kashan evlerinin, özellikle avlunun varlığı ve konumu temel alınarak genel mimari karakterleri tartışılmıştır. Sonrasında, seçilen vi evler, mekansal organizasyonu açıklamaya yardımcı olan şematik analizler sonucunda sınıflandırılmış ve değerlendirilmiştir. Ayrıca, mekan analizleri, mekansal sentaks (space syntax) metodu izlenerek yapılmıştır. Böylelikle, konutların sentatik bilgileri, sonuçlar ve karşılaştırılmalı tartışmalarda, avlunun konut biçimlenmesindeki rolü belirlenmiştir. Sonuç bölümü olan beşinci kısımda, bu çalışma kapsamında elde edilen sonuçlar ve Kashan şehri geleneksel konut mimarisinin önemi ve çağdaş mimari tasarımlar elde etmek için içerdiği ipuçları vurgulanmıştır. Bu bilgiler ışığında, geleneksel Kashan evleri ve belirlenen özgün mimari karakteristikleri, mimari sürekliliği sağlamak ve kentin kimliğini korumak için sürdürülebilir olmalıdır. Anahtar kelimeler: Mekansal Organizasyon, Avlu, Geleneksel Evler, Kashan, Iran.
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Supervisor: Prof. Dr. Özgür Dinçyürek.
Keywords: Architecture; Traditional Houses-Architecture-Kashan (Iran); Spatial Organization; Courtyard; Traditional Houses; Kashan; Iran